Do voluntary commons associations deliver sustainable grazing outcomes? An empirical study of England - LARCOM, Shaun (Institutional Knowledge at Singapore Management University, 2018)
In 1965, the Commons Registration Act came into force in England and Wales. The Act led to the removal of the capacity of commoners to regulate the intensity of grazing via traditional legal means. From this policy shock a number of voluntary commons associations were formed. These voluntary groups relied on their members to agree upon how the commons should be managed. Using two-stage least squares regression analysis we find that commons governed by these associations are much more likely to produce sustainable grazing outcomes. These results are robust to the existence of a variety of controls, including overlapping institutional frameworks. Importantly, they highlight the ability of voluntary environmental organisations to deliver sustainable environmental outcomes.